دراسة تطبيقية للمضاربة في الودائع المصرفية لمصرف جائز بنيجيريا: Profit sharing contract (mudarabah) in bank deposits of jāiz bank in Nigeria: An Analytical and Jurisprudential Study - Ridwan Ayomide Akanbi; Busari, Saheed Abdullahi (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يُعتبر مصرف جائز بنيجيريا البنك الإسلامي الرائد بأنشطة مالية ذات أهمية للاقتصاد الإسلامي، فهذا مما يثير حاجة متزايدة لفحص منتجاته وخدماته من خلال دراسات أكاديمية وفقهية. وقد أثارت الإشكالية المدروسة خلال هذه الورقة البحثية، توصية غير واحد من الورقات البحثية قبلها إلى التشبث بالضوابط المالية الإسلامية فيما يتعلق بعملياته. ولذلك استحسن الباحث التركيز على خدمة المضاربة لدا مصرف جائز، لما فيها من إشكالية كون رأس مال المضاربة ههنا مودعا في حساب توفيري لا استثماري مما يطرح إشكالا على المعاملات التجارية المجراة في نطاق خدمة المضاربة. وذلك لأن من المنطقي لرأس مال المضاربة أن يُمَكَّن العامل منها لمدة يتمكن فيها من القيام بمهام التجارة من تبايع وتقابض حتى ينض المال. واتكالا على المقابلات الشخصية، فقد تم تحليل البيانات النوعية التي جمع على منهج التحليل الموضوعي (Thematic analysis) عبر قناة منهجي الاستقرائي والاستنباطي (Inductive and deductive approach). وبعد دراسة الموضوع خلال مسألتين فقهيتين، توصل الباحث إلى كون الإشكال زائلا باعتبار كون الزبون حرا في ماله المودع في الحساب التوفيري ولا يطبق المصرف عليها أحكام المضاربة إلا عند إبقاء الزبون لمبلغ ولمدة يمكن للمصرف التجارة بها. كما يقترح الباحث على البحوث المستقبلية أن تغطي جانب المحاسبة المالية للموضوع للتدقيق في حقيقة التنضيض الحكمي واستمرارية عقد المضاربة المبحوث فيهما خلال هذا البحث من الناحية الفقهية. ABSTRACT Jaiz Bank can be regarded as the pioneer of Islamic banks in Nigeria, playing a crucial role in Islamic financial activities and sparking a growing need for academic and jurisprudential evaluation of its services. This research paper addresses a common recommendation by past research papers to strictly scrutinise the Islamic financial regulations in its operations. Consequently, the researcher focuses on Jaiz Bank's Mudarabah service, which poses a challenge due to the placement of Mudarabah capital in a savings account rather than an investment account, complicating commercial transactions within this service. It is seen as reasonable for Mudarabah capital to be accessible to entrepreneurs for a period allowing trade activities until capital matures. Using thematic analysis with both inductive and deductive approaches based on personal interviews, qualitative data was analysed. After studying the research gap under the scope of two jurisprudential questions, the researcher concluded that the issue could be resolved, considering the depositor's ownership of funds in the savings account and the application of Mudarabah rules only when funds are retained for a period allowing trade. Additionally, the researcher suggests future studies should examine the financial accounting aspect to assess proper shariah compliance and the ongoing validity of the Mudarabah contract explored in this research, from a jurisprudential perspective.